1998
DOI: 10.1021/es980296x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Transformation of β-Hexachlorocyclohexane by Methanogenic Granular Sludge and Soil Microflora

Abstract: β-Hexachlorocyclohexane (β-HCH) was microbiologically transformed under anaerobic conditions by methanogenic granular sludges from upflow anaerobic sludge blanket (UASB) reactors fed with methanol, volatile fatty acids (VFA), or sucrose as substrates. These sludges, which had not priorily been exposed to β-HCH transformed β-HCH to benzene and chlorobenzene. Usually 2-3 times as much benzene as chlorobenzene was formed. The transformation rates ranged from 0.37 to 0.46 β-HCH (g of volatile suspended solids (VSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 43 publications
2
31
2
Order By: Relevance
“…However, reduction of 13 mg kg -1 day -1 was obtained under methanogenic conditions. Van Eekert et al (1998) have reported the removal of -HCH from a sandy soil containing low concentration of the isomer in slurries where lactate or sulfide had been added to reduce redox potential. Degradation of HCH was faster under anoxic conditions and that microbial degradation was primary route of HCH disappearance from soil (MacRae et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…However, reduction of 13 mg kg -1 day -1 was obtained under methanogenic conditions. Van Eekert et al (1998) have reported the removal of -HCH from a sandy soil containing low concentration of the isomer in slurries where lactate or sulfide had been added to reduce redox potential. Degradation of HCH was faster under anoxic conditions and that microbial degradation was primary route of HCH disappearance from soil (MacRae et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of anaerobic HCH degradation reported the accumulation of chlorobenzene and benzene (24,98,179), although Quintero et al (140) detected only traces of these metabolites, and Jagnow et al (64) reported the complete degradation of ␥-HCH at least to chloride and chloride-free metabolites in mixed and pure cultures of Clostridium species. There have been other reports of the anaerobic mineralization of benzene (41,147), but we are unaware of other reports of the anaerobic degradation of chlorobenzene.…”
Section: Anaerobic Degradationmentioning
confidence: 99%
“…2). The percentage degradation of b-HCH is less than , 1990;Johri et al, 1998;Van Eekert et al, 1998). HCH biodegradation was initially thought to be an anaerobic process (Sethunathan et al, 1983;MacRae et al, 1984) and reductive dechlorination of the four commonly found HCH isomers (a-, b-, c-, d-HCH) had been observed under anoxic conditions in soil microcosms (Jagnow et al, 1977), soil slurries (MacRae et al, 1984) and pure cultures (Jagnow et al, 1977).…”
Section: The Effect Of Fe 0 On the Degradation Of Hchsmentioning
confidence: 99%
“…Many pesticides, such as b-HCH and DDX are normally considered persistent in aerobic environments, are not persistent under anaerobic conditions (Aislabie et al, 1997;Van Eekert et al, 1998). Therefore, generating a reduced environment in water, soils and sediments may facilitate the degradation of organochlorine pesticides (OCPs) (Satapanajaru et al, 2006).…”
Section: Introductionmentioning
confidence: 99%